Methylation‐dependent transcriptional regulation of crescentin gene (creS) by GcrA in Caulobacter crescentus. Issue 1 (10th April 2020) - Mohapatra, Saswat S.; Fioravanti, Antonella; Vandame, Pauline; Spriet, Corentin; Pini, Francesco; Bompard, Coralie; Blossey, Ralf; Valette, Odile; Biondi, Emanuele G.
Abstract: In Caulobacter crescentus the combined action of chromosome replication and the expression of DNA methyl‐transferase CcrM at the end of S‐phase maintains a cyclic alternation between a full‐ to hemi‐methylated chromosome. This transition of the chromosomal methylation pattern affects the DNA‐binding properties of the transcription factor GcrA that controls the several key cell cycle functions. However, the molecular mechanism by which GcrA and methylation are linked to transcription is not fully elucidated yet. Using a combination of cell biology, genetics, and in vitro analysis, we deciphered how GcrA integrates the methylation pattern of several S‐phase expressed genes to their transcriptional output. We demonstrated in vitro that transcription of ctrA from the P1 promoter in its hemi‐methylated state is activated by GcrA, while in its fully methylated state GcrA had no effect. Further, GcrA and methylation together influence a peculiar distribution of creS transcripts, encoding for crescentin, the protein responsible for the characteristic shape of Caulobacter cells. This gene is duplicated at the onset of chromosome replication and the two hemi‐methylated copies are spatially segregated. Our results indicated that GcrA transcribed only the copy where coding strand is methylated. In vitro transcription assay further substantiated this finding. As several of the cell cycle‐regulated genes are also under the influence of methylation and GcrA‐dependent transcriptional regulation, this could be a mechanism responsible for maintaining the gene transcription dosage during the S‐phase. Abstract : Caulobacter crescentus is a model organism for the study of the bacterial cell division. Each cycle the cell divides asymmetrically producing two different cell types. The typical cell curvature of Caulobacter is due to the presence of a cytoskeletal protein named crescentin. Here, we showed that crescentin production depends on the methylation of DNA and the transcription factor GcrA. Transcription of creS takes place at the polar regions where the gene is located. Methylation and GcrA indeed create a mechanism that confine in time and space the expression of crescentin.